Hubungan Wasting dengan Kejadian Stunting pada Balita di Wilayah Kerja UPTD Puskesmas Tarus Tahun 2026 - Marthin Dethan; Intje Picauly (Universitas Pahlawan Tuanku Tambusai, 2026)
Nutritional issues in toddlers, particularly wasting and stunting, remain a public health challenge due to their impact on child growth and development. Wasting, a form of acute malnutrition, is suspected to be a risk factor for chronic stunting. This study aims to analyze the relationship between nutritional status (wasting) and the incidence of stunting in toddlers in the Tarus Community Health Center (UPTD) work area in 2026. This study used an observational analytical design with a cross-sectional approach. The data used were secondary data from the e-PPGBM application, with a sample of 472 toddlers drawn using a total sampling technique. Data analysis was performed using univariate and bivariate methods using the Chi-square test with a 95% confidence level (α = 0.05). The results showed that the prevalence of stunting was 8.7% and wasting was 9.5%. The proportion of stunting was higher in toddlers with wasting (24.4%) compared to those without wasting (7.0%). The Chi-square test results showed a p-value of 0.000 (p < 0.05), indicating a significant relationship between wasting nutritional status and stunting in toddlers. The conclusion of this study is that there is a significant relationship between wasting and stunting, with wasting being a risk factor for stunting. Therefore, early detection and optimal management of wasting are needed as a strategy for stunting prevention through integrated nutritional interventions at the primary health care level.